Effect of light during broiler mothers’ eggs incubation on embryos growth and hatched chicks weight (Latakia University Journal -Biological Sciences Series, 2022)
To study the importance of adding LED light to the artificial incubation process, and the extent of broiler embryos response to some lighting systems, and to assess the extent of the impact of these systems on both embryonic development, and the quality of hatched chicks, and some hatching standards, a study was conducted on 315 fertilized egg of hybrid broiler mothers’ (Hubbard FLEX), where the eggs were randomly divided into three different treatments according to the lighting system applied during incubation (continuous darkness 0L:24D, 12hours of light versus 12hours of darkness 12L:12D, continuous light 24L:0D), with 105 eggs for one treatment, and the single treatment was divided into three replicates by 35 eggs per one, at the same incubation and post-hatching conditions for all treatments.The results showed a significant increase (P